An Improved Method for Generating Cutter Points Based on Required Form Accuracy of the Machining Surface. (22nd April 2015) - Ji, Shijun; Yu, Huijuan; Zhao, Ji
Abstract : Recently, freeform surfaces are widely used in optical field. Fabrication of freeform surface optics needs high machining accuracy and high efficiency simultaneously. Using the present ultraprecision manufacturing technologies, the form accuracy of freeform surfaces can reach submicrometric or even nanometer range but at the cost of low efficiency; moreover, the form accuracy cannot be predicted; the number and the position of cutter points cannot be accurately controlled before practical machining. A novel strategy of cutter points distribution is proposed in the paper, which is based on the required accuracy of the freeform surface and the machining efficiency can be improved by eliminating redundant cutter points on the processing trajectory. The new idea is detailed, simulations are conducted, and experiments are done to verify the feasibility of the proposed method in fabricating two sinusoidal ring surfaces.